Analysis of Online Learning Student Activities Using the Problem Based Learning (PBL) Model through Lesson Study - Sari, Nurratri Kurnia; Wicaksana, Muhlis Fajar (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Online lectures so far have been less effective and being less attractive to students often makes students passive, bored, and not enthusiastic about attending lectures. Students are not active in the lecture process will not achieve a learning goal. This study aims to describe the analysis of student activities with the Problem Based Learning (PBL) model through lesson study in online learning. The research method used is a qualitative descriptive analysis method. Data validity techniques use triangulation techniques. Data is collected by observing techniques and recording student activities during online learning. Data analysis techniques present calculations in the proportion of observations on student activity. The implementation of research is carried out based on lesson study activities, namely plan, do and see. In the planning stage, model lecturers and observers agreed that the problem to be solved was online learning with the Problem Based Learning (PBL) model. Activities that will be observed 5 aspects, namely oral activities, listening activities, writing activities, mental activities and emotional activities. At the do stage, model lecturers carry out learning through the PBL model. The orientation of the problem is centred on the observation of integrated thematic learning in elementary schools. While the see stage shows the profile of student learning activities in online learning through the PBL model, namely oral activities of 86.1, listening activities of 96.3, writing activities amounted to 89.4, mental activities amounted to 86, and emotional activities amounted to 80.6. Based on the results of the research above, student activity through the lesson study-based PBL model can be categorized as high. This is inseparable from the collaborative role of lecturers in organizing learning, from planning to evaluation.